THE FEASIBILITY OF A PERSONAL LEARNING ENVIRONMENT (PLE) TO SUPPORT ACADEMIC WRITING: ESL PRE-SERVICE TEACHERS’ PERSPECTIVES - Noraini Said; Megawati Soekarno; Nik Zaitun Nik Mohamed; Chelster Sherralyn Jeoffrey Pudin (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
A recent trend has highlighted the need for a personal learning environment (PLE) in education as a system that helps learners take control of and manage their own learning. The current system which focuses on standardized learning support in the form of Learning Management System (LMS) is seen as restrictive and does not allow to accommodate the different needs of learners. Therefore, more language educators have started developing their own PLEs by focusing on two crucial elements: supporting learners’ needs and allowing more learner control. This paper presents an attempt to explore ESL pre-service teachers’ experience via PLE designed to support their writing needs. The researchers hoped that such a positive experience would influence the teachers’ pedagogical strategies and approaches in their teaching once they go into practice. In this qualitative case study, thirty-six third year ESL pre-service teachers at a tertiary education institution embarked on a fourteen-week course via the PLE. Qualitative data were gleaned from focus group discussion transcripts and written reflections. Thematic analysis was used to analyse the qualitative data. Overall, students have positive perceptions towards the PLE by detailing its benefits and usefulness. They also narrated some challenges and proposed suggestions to ensure prolonged engagement. The findings give support to the use of PLE, especially the instructor-made innovation for teaching and learning which allows more learner control and access.